The Effect of Cruel Punishments in The Mental Hospital To Susanna’s Depression in Susanna Kaysen’s Girl, Interrupted! - Melissa Elaine Saputra; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This paper is basically a study of depression. Through the study on Susanna Kaysen’s Girl, Interrupted!, I intend to analyze the effects of cruel punishment in the mental hospital to Susanna Kaysen, the main character in the novel. In order to fulfill the goal of this thesis, I use psychological theory on depression to analyze the novel. Finally, I conclude that Susanna becomes more depressed after she enters the mental hospital and sees the cruel punishment in there. The cruel punishments can be classified into two groups. They are mental and physical torture. In the novel, Susanna experiences both of them that make her feel more depressed than before she enters the mental hospital. In other words, watching the cruel punishment or torture can make a healthy person becomes depressed and depressed person becomes more depressed. Therefore, a person should avoid watching anything cruel in the television, radio, newspaper, and society so that they will not get depressed or more depressed by it